Development of a method for combined control of thickness, tension and flatness of strips in continuous cold rolling to reduce longitudinal thickness variation and nonflatness - Hongyi, Wu; Prykhodko, Ihor; Peng, Zuo; Debin, Wang (Eastern-European Journal of Enterprise Technologies, 2025)
The object of study is the process of continuous cold rolling of strips, in which the parameters of thickness, tension and flatness of the metal. Obtaining high flatness of thin strips during cold rolling at industrial 4-stand mills, where the last stand realizes significant degrees of compression in the working rolls with a diameter of up to 500 mm, when implementing the mode with a constant rolling force causes an increase in the longitudinal thickness deviation of strips. And the accentuated obtaining of minimum longitudinal thickness variation of strips leads to a change in the rolling force and as a result, due to the change in the deflection of rolls worsens the flatness of strips. The results of control actions can worsen both main quality indicators at the same time. The known methods of thickness and flatness control during cold rolling are analyzed and an alternative method of combined influence on these quality indicators is proposed. An optimization criterion is proposed. The quantitative estimation of the achieved simultaneous improvement of accuracy in thickness and flatness of strips as a result of the combined impact due to the realization of the optimal combination of interrelated control actions is performed. The method and algorithm of combined influence on thickness, tension and flatness of strips taking into account speed capabilities of actuators and their current position are proposed to reduce longitudinal fluctuations of thickness and nonflatness. Simultaneous decrease of strip nonflatness and longitudinal thickness fluctuations is explained by the optimal combination of regulation channels. This method can be used on modern mills based on local systems of automatic control of strip thickness and flatness. Numerical estimations of probable practical results achieved when using the proposed method. A simultaneous reduction in strip flatness of 20–30 % and the provision of limited thickness limit deviations to EN 10131(S) in at least 80 % of the inter-grade transitions are expected